Home is where your politics are : queer activism in the U.S. South and South Africa - Scott, Jessica A. (Rutgers University Press, 2024)
Home Is Where Your Politics Are is a transnational consideration of queer and trans activism in the US South and South Africa. Through ethnographic exploration of queer and trans activist work in both places, Jessica Scott paints a vibrant picture of what life is like in relation to a narrative that says that queer life is harder, if not impossible, in rural areas and on the African continent. The book asks questions like, what do activists in these places care about and how do stories about where they live get in the way of the life they envision for the queer and trans people for whom they advocate? Answers to these questions provide insight that only these activists have, into the complexity of locally based advocacy strategies in a globalized world.
Description based upon print version of record.
Keywords: LGBT activism -- Southern States.; LGBT activism -- South Africa.; Sexual minorities -- Political activity -- Southern States.; Sexual minorities -- Political activity -- South Africa.; SOCIAL SCIENCE / General